DETECTION OF FINANCIAL DISTRESS AS AN EFFORT EARLY WARNING SYSTEM FOR COAL MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2019 – 2021 - Ariowibowo, Tito Setio; Brahmayanti, Ida Ayu (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to detect financial distress in coal mining companies listed on the IDX for the 2019-2021 period as an early warning system based on indicators of the BOPO ratio, sales volume growth, liquidity ratio, leverage ratio, and profitability ratios. The population used in this study were 27 coal mining companies. The type of research used is quantitative research through secondary data sources in the form of published financial reports that have been audited by public accountants. The results of this study are divided into 3, namely companies that are not detected in financial distress, companies that are not detected, and companies that are detected in financial distress. From this analysis, there were 9 companies not detected financial distress, 0 companies not detected, and 18 companies detected financial distress. Keywords: Early Warning System, Financial Distress, BOPO Ratio, Sales Volume, Liquidity Ratio, Leverage Ratio, and Profitability Ratio